Feodalité y féodalisme antes del medievalismo: Presencia y ausencia de dos conceptos en la historiografía francesa, 1828-1870 - Diego Carlo Améndolla Spínola (L'Atelier du CRH)
The article aims to contribute to the critical discussion about the meaning, usefulness, and historicity of the concepts féodalité and féodalisme during the 19th-Century. Based on the postulates of the conceptual history, the present paper analyzes the mentioned notions in the historiographical works of François Guizot, Sismonde de Simondi, Jules Michelet y Augustin Thierry, which were produced between 1828 and 1870, that is, in the year between the Restauration and the Third Republic.